Gonadotropin-Releasing Hormone and Adipokinetic Hormone Signaling Systems Share a Common Evolutionary Origin - Lindemans, Marleen; Beets, Isabel; Janssen, Tom; Temmerman, Liesbet; Meelkop, Ellen; Schoofs, Liliane (Frontiers in Endocrinology, 2011)
Gonadotropin-releasing hormone (GnRH) is a critical and central hormone that regulates vertebrate reproduction. The high conservation of GnRH signaling within the chordates (deuterostomians) raises the important question as to whether its appearance might date back prior to the divergence of protostomian and deuterostomian lineages, about 700 million years ago. This leads to several important questions regarding the evolution of the GnRH family. Has GnRH been retained in most protostomian lineages? And was regulation of reproduction already a function of ancestral GnRH? The first question can undoubtedly be answered affirmatively since several GnRH-like sequences have been found in wide variety of protostomian and deuterostomian phyla. However, based on their different primary functions in different phyla – which implies a less unanimous answer on the second question – consistency in the nomenclature of this peptide family has been lost. A comparative and phylogenetic approach shows that the ecdysozoan adipokinetic hormones (AKHs), lophotrozoan GnRHs and chordate GnRHs are structurally related and that they all originate from a common ancestor. This review supports the view that the AKH-GnRH signaling system probably arose very early in metazoan evolution, prior to the divergence of protostomians and deuterostomians.